Living Conditions and the Mental Health and Well-being of Refugees : Evidence from a Large-Scale German Survey - Lena Walther; Lukas M. Fuchs; Jürgen Schupp; Christian von Scheve (Journal of Immigrant and Minority Health, 2020)
Refugees are at an increased risk of mental health problems and low subjective well-being. Living circumstances in the host country are thought to play a vital role in shaping these health outcomes, which, in turn, are prerequisites for successful integration. Using data from a representative survey of 4325 adult refugees who arrived in Germany between 2013 and 2016, we investigated how different living conditions, especially those subject to integration policies, are associated with psychological distress and life satisfaction using linear regression models. Our findings show that an uncertain legal status, separation from family, and living in refugee housing facilities are related to higher levels of distress and decreased life satisfaction. Being employed, contact to members of the host society, and better host country language skills, by contrast, are related to reduced distress and higher levels of life satisfaction. These associations should inform decision making in a highly contested policy area.
Keywords: 330; Refugees; Mental health; Well-being; Integration